Vegetative development of cultivars Coffea arabica L. grafted in Apoatã IAC 2258 (Coffea canephora Pierre ex A. Froehner) - Dominghetti Ferreira, André; Machado Rezende, Ramiro; Rodrigues Carvalho, Gladyston; José Guimarães, Rubens; Ferreira de Figueiredo, Tiago (Coffee Science - ISSN 1984-3909, 2011)
The use of grafting on coffee plants, besides conferring greater tolerance to nematodes, has been shown to influence plant growth and development. The aim of the present study is to evaluate vegetative growth of different cultivars of Coffea Arabica L. grafted on Apoatã IAC 2258 (Coffea canephora Pierre ex A. Froehner). The experiment was conducted in a greenhouse at the Universidade Federal de Lavras, using pots with corrected soil acidity and free of nematodes. We used a factorial 7 x 3 + 2, with seven cultivars of C. Arabica (Palma II, Catucaí 2SL, MG 6851, Obatã IAC 1669-20, Acauã, Topazio MG 1190 and Paraiso MG H 419-1), three types of seedlings (ungrafted, self grafted and grafted Apoatã IAC 2258 ) and two additional (self grafted Apoatã and ungrafted Apoatã). With these results we conclude that the technique of grafting had no influence on the formation of coffee seedlings, since self grafted seedlings showed no statistical differences with respect to ungrafted seedlings. However, the root stock Apoatã had a negative effect, because the grafted seedlings were inferior to those ungrafted in all evaluations, regardless of the C. arabica cultivar grafted. When comparing self grafted Apoatã with grafted cultivars of Apoatã as to root dry mass, the cultivars Catucaí 2SL and Paraiso were able to promote the development of the root system of rootstocks similar to self grafted Apoatã.